Nonlinear and parametric phenomena : theory and applications in radiophysical and mechanical systems - Damgov, Vladimir (World Scientific series on nonlinear science. Monographs and treatises, 2004)
The book comprises a broad panorama of phenomena occurring in four major classes of radiophysical and mechanical systems linear, nonlinear, parametric, and nonlinear-parametric. An analytical technique for the broad circle of issues under consideration is developed. It is presented in a user-friendly form, allowing its further direct application in research practices. Analytical methods are presented for investigating modulation-parametric and nonlinear systems, oscillating systems with periodic and almost periodic time-dependent parameters, effects of adaptive self-organization in coupled re.